2019
DOI: 10.1097/md.0000000000016784
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy for the treatment of frozen shoulder

Abstract: Background: Previous clinical trials have reported that physical therapy (PT) can be used for the treatment of frozen shoulder (FS). However, its effectiveness is still inconclusive. In this systematic review study, we will aim to evaluate the effectiveness and safety of PT alone for the treatment of FS. Methods: The following electronic databases will be searched from the inception to the present to identify any eligible studies focusing on PT for the treatment of FS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Quite a few studies have reported effectiveness of these physical therapy modalities for treating adhesive capsulitis patients. [15][16][17] Current study was no different and reported that conventional physical therapy techniques can be used to manage patients with adhesive capsulitis. Physical therapy decreases pain, improves ROM and therefore increases functional abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Quite a few studies have reported effectiveness of these physical therapy modalities for treating adhesive capsulitis patients. [15][16][17] Current study was no different and reported that conventional physical therapy techniques can be used to manage patients with adhesive capsulitis. Physical therapy decreases pain, improves ROM and therefore increases functional abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapy interventions offered for frozen shoulder include hydrocolloid packs, infrared radiation, shortwave diathermy, ultrasound, laser, and physical exercises [ 19 ]. Extracorporeal shockwave therapy (ESWT) is one of the most successful treatment modalities used in physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with adhesive capsulitis experience a low quality of life due to their passive and active shoulder mobility limitations [ 20 ]. Health-related quality of life is a concept that encompasses subjective satisfaction with physical, psychological, economic, spiritual, and social functions in an individual’s daily life, representing an individual’s physical and mental health status well [ 21 ].…”
Section: Introductionmentioning
confidence: 99%